Women, healthcare leadership and societal culture: a qualitative study - Kalaitzi S; Czabanowska K; Azzopardi-Muscat N; Cuschieri L; Petelos E; Papadakaki M; Babich S (Dove Medical Press, 2019)
Stavroula Kalaitzi,1 Katarzyna Czabanowska,1,2 Natasha Azzopardi-Muscat,3 Liliana Cuschieri,4 Elena Petelos,5,6 Maria Papadakaki,7 Suzanne Babich1,8 1Department of International Health, Care and Public Health Research Institute (CAPHRI), Faculty of Health, Medicine and Life Sciences, Maastricht University, Maastricht, the Netherlands; 2Department of Health Policy and Management, Institute of Public Health, Faculty of Health Sciences, Jagellonian University, Krakow, Poland; 3Department of Health Services Management, Faculty of Health Sciences, University of Malta, Msida, Malta; 4Department for Policy in Health, Ministry for Health, Valletta, Malta; 5Clinic of Social and Family Medicine, Department of Social Medicine, School of Medicine, University of Crete, Iraklion, Greece; 6Department of Health Services Research, Care and Public Health Research Institute (CAPHRI) Faculty of Health, Medicine and Life Sciences, Maastricht University, Maastricht, the Netherlands; 7Department of Social Work, School of Health and Social Welfare, Technological Educational Institute of Crete, Iraklion, Greece; 8Department of Health Policy and Management, Richard M. Fairbanks School of Public Health, Indianapolis, IN, USA Purpose: Women leaders encounter societal and cultural challenges that define and diminish their career potential. This occurs across several professions including healthcare. Scant attention has been drawn to the discursive dynamics among gender, healthcare leadership and societal culture. The aim of this study is to assess empirically gendered barriers to women’s leadership in healthcare through the lens of sociocultural characteristics. The comparative study was conducted in Greece and Malta. The interest in these countries stems from their poor performance in the gender employment gap and the rapid sociocultural and economic changes occurring in the European-Mediterranean region.Subjects and methods: Thirty-six individual in-depth interviews were conducted with healthcare leaders, including both women and men (18 women and 18 men). Directed content analysis was used to identify and analyze themes against the coding scheme of the Barriers Thematic Map to women’s leadership. Summative content analysis was applied to quantify the usage of themes, while qualitative meta-summative method was used to interpret and contextualize the findings.Results: Twenty and twenty-one barriers to women’s leadership were identified within the Greek and Maltese healthcare settings, respectively. Prevailing barriers included work/life balance, lack of family (spousal) support, culture, stereotypes, gender bias and lack of social support. Inter-country similarities and differences in prevalence of the identified barriers were observed.Conclusion: The study appraised empirically the gendered barriers that women encounter in healthcare leadership through the lens of national sociocultural specificities. Findings unveiled underlying interactions among gender, leadership and countries’ sociocultural contexts, which may elucidate the varying degrees of strength of norms and barriers embedded in a society’s egalitarian practices. Cultural tightness has been found to be experienced by societal dividends as an alibi or barrier against sociocultural transformation. Findings informed a conceptual framework proposed to advance research in the area of women’s leadership. Keywords: gendered barriers, sociocultural contexts, Greece, Malta, directed content analysis